Transformasi Digital di Dunia Pendidikan: Integrasi Teknologi dalam Kurikulum Sekolah - Judijanto, Loso; Rosdiana Mata; Hanif Ramadhan Fahmi Putra (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2025)
Digital transformation in education through the integration of technology in the school curriculum has a significant impact in improving the accessibility, flexibility, and effectiveness of the teaching and learning process. The study in this research uses the literature method. The results show that technology enables a more interactive, personalized, and adaptive learning experience by providing fun digital learning tools and efficient evaluation methods. Students can learn anytime and anywhere, while teachers can provide timely feedback and develop teaching strategies based on analyzing student performance data. However, challenges such as digital distraction, technology dependency and teacher training needs must be overcome to ensure maximum benefits from this transformation. A balance between technology and traditional methods and continuous support for educators are key to successfully implementing technology in education.